The Floodplain Woods of Tuscany. Issue 2 (9th December 2020) - Gennai, M.; Carnicelli, S.; Dell'Olmo, L.; Gabellini, A.; Giunti, M.; Lazzaro, L.; Lucchesi, F.; Monacci, F.; Viciani, D.; Foggi, B.
ABSTRACT: The contraction of lowland forests throughout Europe began in remote times and then intensified strongly with land reclamation by agriculture and urbanization during the first half of the last century. We present a map of the Floodplain Woods of Tuscany on a scale of 1:300, 000 as a synthesis of that built at the scale of 1:10, 000 and the methods used to obtain it. Nearly 90% of the patches contain habitats of concern to conservation, according to the Habitat Directive. The Tuscan Floodplain Woods remained prevalent in coastal areas, where some levels of protection are guaranteed by the presence of several protected areas, whereas they have practically vanished in the other parts of the regional territory. The resulting patches are very small and distant from each other, so only in-depth management of all potential floodplain forest areas, taking into consideration patches for their regeneration, can be useful to assure their conservation.